2019
DOI: 10.1016/s2095-3119(17)61858-6
|View full text |Cite
|
Sign up to set email alerts
|

Invasion genetics of alien insect pests in China: Research progress and future prospects

Abstract: An unwelcome side effect of the globalization of the world's economy and dramatic increase in human mobility and trade has been a marked increase in species invasions that have posed severe threats to the ecological, economic, and/or social stability of the introduced regions. In this review, we analyzed the application of molecular markers in invasion genetics of invasive alien insect pests (IAIPs) in China based on a bibliometric survey. Our report discusses the considerable progress that has been made durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…HAV1, HMLV3, HPiV55, HTLV 2, WAV1, WIV21, SFV4, and WFV5 were reported originally from Hubei Province in China [38,46] and Pernambuco virus was reported from Brazil [34]. The high levels of nucleotide sequence identity among virus isolates from North America, Brazil, and China may be the result of the frequent exchange of insects between the continents [73,74]. The abundance of sequence reads for some of these viruses suggests that they replicate within soybean thrips and may indicate that these viruses have broad host ranges, which may have facilitated their spread across broad geographic ranges.…”
Section: Discussionmentioning
confidence: 99%
“…HAV1, HMLV3, HPiV55, HTLV 2, WAV1, WIV21, SFV4, and WFV5 were reported originally from Hubei Province in China [38,46] and Pernambuco virus was reported from Brazil [34]. The high levels of nucleotide sequence identity among virus isolates from North America, Brazil, and China may be the result of the frequent exchange of insects between the continents [73,74]. The abundance of sequence reads for some of these viruses suggests that they replicate within soybean thrips and may indicate that these viruses have broad host ranges, which may have facilitated their spread across broad geographic ranges.…”
Section: Discussionmentioning
confidence: 99%
“…There are generally two types of sampling that occur in invasive genomic studies. First, there is process variance, due to variations in genetic metrics caused by the number of individuals introduced, the diversity and differentiation of the source population(s), multiple introductions, genetic drift, and natural dispersal [44][45][46]. Second, there is sampling variance, caused by variation in allele frequencies when a subset of individuals (the sample) is drawn from the population [1,23,44].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we confirmed that this resampling method is effective and robust, but it may be necessary to assess the appropriate sample size for each invasive species prior to the characterization of their invasion genetics. The main reason is these estimates can be affected by many factors in evolutionary process including the bottleneck effect, founder effect, and bridgehead effect [46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that invasion genetics can be affected by many factors including the bottleneck effect, founder effect, bridgehead effect, multiple introductions, genetic turnover, gene flow, and hybridization (Chu, Qu, & Guo, ). Considering the potential effects of these factors, it is imperative to analyze the sampling scheme when studying population genomics of invasive species.…”
Section: Discussionmentioning
confidence: 99%